Heart failure disease management: a systematic review of effectiveness in heart failure with preserved ejection fraction. (24th January 2020) - Kalogirou, Fotini; Forsyth, Faye; Kyriakou, Martha; Mantle, Rhys; Deaton, Christi
Abstract: Aims: Heart failure with preserved ejection fraction (HFpEF) poses a substantial challenge for clinicians, but there is little guidance for effective management. The aim of this systematic review was to determine if there was evidence that disease management programmes (DMPs) improved outcomes for patients with HFpEF. Methods and results: A systematic review of controlled studies in English or Greek of DMPs including patients with HFpEF from 2008 to 2018 was conducted using CINAHL, Cochrane, MEDLINE, and Embase. Interventions were assessed using a DMP taxonomy and scored for complexity and intensity. Bias was assessed using the Cochrane Collaboration tool. Initial and updated searches found 6089 titles once duplicates were removed. The final analysis included 18 studies with 5435 HF patients: 1866 patients (34%, study ranges 18–100%) had potential HFpEF (limited by variable definitions). Significant heterogeneity in terms of the population, intervention, comparisons, and outcomes prohibited meta‐analysis. Statistically significant or positive trends were found in mortality, hospitalization rates, self‐care ability, quality of life, anxiety, depression, and sleep, but findings were not robust or consistent. Four studies reported results separately for study‐defined HFpEF, with two finding less positive effect on outcomes. Conclusions: Varying definitions of HFpEF used in studies are a substantial limitation in interpretation of findings. The reduced efficacy noted in contemporary HF DMP studies may not only be due to improvements in usual care but may also reflect inclusion of heterogeneous patients with HFpEF or HF with mid‐range EF who may not respond in the same way as HFrEF to individual components. Given that patients with HFpEF are older and multi‐morbid, DMPs targeting HFpEF should not rely on a single‐disease focus but provide care that addresses predisposing and presentation phenotypes and draws on the principles of comprehensive geriatric assessment. Other components could also be more targeted to HFpEF such as modification of lifestyle factors for which there is emerging evidence, rather than simply continuing the model of care used in HFrEF. Based on current evidence, HF DMPs may improve mortality, hospitalization rates, self‐care, and quality of life in patients with HFpEF; however, further research specifically tailored to appropriately defined HFpEF is required.